Peran Guru Akhlak dalam Membentuk Karakter Religius Peserta Didik di SMP Muhammadiyah 3 Purwokerto - Saras Aprilia; Makhful Makhful (UM Purwokerto Press, 2023)
The purpose of this study was to determine the role of moral teachers in shaping the religious character of students at SMP Muhammadiyah 3 Purwokerto and to find out the inhibiting and supporting factors of moral teachers in shaping the religious character of students at SMP Muhammadiyah 3 Purwokerto. This research is a type of field research with data collection techniques, namely interviews, observation, and documentation. Data analysis used primary data from the results of interviews with moral teachers. The results showed that the role of the moral teacher at SMP Muhammadiyah 3 Purwokerto in shaping the religious character of students, among others, as educators and teachers, was by conveying material according to religious teachings, and having a good personality that students could later emulate as their role models, and continue to guide and remind students to always carry out Islamic coaching. While the supporting factors in the formation of the religious character of students are that almost all teachers in the school can attend every religious subject as well as the existence of supporting religious facilities. While the inhibiting factors are that there are still many students who cannot recite the Koran or pray, the learning system changes frequently during the COVID-19 pandemic, and students have different characters so that sometimes it is quite difficult for teachers in the learning process.